Correlations Between Mandibular Third Molars to Inferior Alveolar Nerve Locations in Vietnamese Population - Pham Ngoc Anh Thu; Tran Nhut Thao Trang; Florenly; Novelya (Biomedical Journal of Indonesia, 2021)
One of the probable complications in mandibular third molar extraction is the damage to the inferior alveolar nerve (IAN). Calculating the distance between IAN and third mandibular can decrease the complication risk. In this study, cone beam computed tomography (CBCT) scans were used to evaluate several factors related to the positional relationship between mandibular third molar and IAN in the Vietnamese population. One-hundred-seventy-eight CBCT scans were collected from dental clinics at Ho Chi Minh City, from 1st January 2018 to 28th February 2021. Only 100 scans were included in this study, 55 scans of female and 45 scans of male patients. The age of the patients ranged from 19 to 59 years old. From this study, the most common location of IAN relative to the roots of the mandibular third molar was on the apical side (60.5%), followed by the buccal side (21.5%), the lingual side (16%), and the least common located between the roots (2%). Overall, the mean distance between mandibular third molar roots to IAN was 3.19 ±1.85mm. There was a significant correlation between the left and right sides of the IAN location, indicating symmetry. Moreover, there is no association was found between gender and the location of IAN.